FORMATION OF THE IMAGE OF THE BODY "I" PRIMARY SCHOOL STUDENTS AS BASICS CONSCIOUS ATTITUDE TO YOUR OWN HEALTH (Pedagogy of Higher and Secondary Education, 2022)
The article analyzes the features of a pupil's body image. Connection between representations of body image and the features of care of health is defined. In particular, at low degree of definiteness of an body image, is schematic image, with high degree of stereotypification, pupils show socially caucausedpupilsa a sed relation to their own health and hygiene rules. It is proved the influence of pupil's emotional development on increase of degree of definiteness of a body image, by inclusion of the elements of Dance Moving Therapy in choreography lessons.
Keywords: structural complete image of the person; body image; consciousness; health of the pupil; dance-moving therapy